Tafsir Ahkam Melalui Kitab al-Maḥṣûl Karya Fakhruddin al-Razi Terhadap Hukum Pernikahan Beda Agama - Mohammad Alfin Niam; Misbahul Huda (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
This paper is a study of tafsir ahkam that examines the ruling on interfaith marriage by using Kitab al-Maḥṣûl by Fakhruddin al-Razi as the main reference. Interfaith marriage remains a relevant issue in the dynamics of modern Muslim society, especially amid the increasing desire to marry people of other religions and the declining interest in the institution of marriage. This research analyzes Qur'anic verses that appear contradictory, such as Surah al-Baqarah [2]: 221 and Surah al-Mumtahanah [60]: 10, which generally prohibit marriage between Muslims and non-Muslims, and Surah al-Mā’idah [5]: 5, which allows Muslim men to marry women from the People of the Book. The study uses a qualitative method with a library-based approach. Al-Razi’s rejection of the absolute authority of ijma’ (consensus) opens up space for more flexible interpretations of Islamic law, taking into account textual evidence, social realities, and the principle of public interest (maslahah). Umar ibn Khattab’s cautious stance on marriage with the People of the Book also highlights the importance of contextual considerations. Based on this analysis, the author concludes that interfaith marriage (with the People of the Book) is not permitted, except in specific urgent circumstances that fulfill a greater public interest, differing from al-Razi’s interpretation in Mafātīh al-Ghayb, which is more permissive toward such marriages.